[RETRACTED] Evaluating the efficacy of Kaempferia Galanga essential oil as a massage medium for accelerating muscle recovery - Manalu, Nimrot; Ibrahim, Ibrahim; Gultom, Siti; Purba, Pangondian Hotliber; Ilham, Zulpikar; Bangun, Sabaruddin Yunis (Jurnal Keolahragaan, 2024)
The editorial board of Jurnal Keolahragaan hereby retracts the article titled “Evaluating the Efficacy of Kaempferia Galanga Essential Oil as a Massage Medium for Accelerating Muscle Recovery” published in Vol. 12 No. 2, due to double publication by the same author(s) in another media. The article has been removed from the current volume and will not be considered as part of the official scholarly record of this journal. We regret any inconvenience this may cause to our readers and authors. The editorial board emphasizes the importance of upholding academic integrity and originality in all published work.